2002
DOI: 10.1590/s0034-75902002000300009
|View full text |Cite
|
Sign up to set email alerts
|

Captação de recursos por fundos de investimento e mercado de ações

Abstract: O presente artigo analisa a relação contemporânea e defasada entre fluxos de entrada e saída de recursos nos fundos de ações no Brasil e o desempenho de alguns ativos fundamentais, tais como o Índice Bovespa, a taxa de câmbio comercial e a taxa de juros no mercado interbancário. Os principais objetivos do trabalho são (1) encontrar evidências de que o fluxo de recursos depende do desempenho desses ativos, com particular atenção para o Índice Bovespa, e (2) verificar se as estatísticas de captação de recursos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
(3 reference statements)
1
8
0
2
Order By: Relevance
“…Ao analisar o mercado de capitais brasileiro, Sanvicente (2002) constata, com base em dados agregados, a forma como a captação de recursos permite explicar os retornos de fundos de investimento. O autor conclui que os fluxos de recursos captados pelos fundos de investimentos influenciam seu desempenho, mas que os volumes investidos nos ativos, embora influentes, não podem ser utilizados como fatores ou critérios para prever retornos.…”
Section: Evoluções Teórica E Empírica Da Avaliação Do Desempenho Paraunclassified
“…Ao analisar o mercado de capitais brasileiro, Sanvicente (2002) constata, com base em dados agregados, a forma como a captação de recursos permite explicar os retornos de fundos de investimento. O autor conclui que os fluxos de recursos captados pelos fundos de investimentos influenciam seu desempenho, mas que os volumes investidos nos ativos, embora influentes, não podem ser utilizados como fatores ou critérios para prever retornos.…”
Section: Evoluções Teórica E Empírica Da Avaliação Do Desempenho Paraunclassified
“…The literature focused on the Brazilian market indicates that the capital allocation flow in stock funds increases when there is a positive variation in the Ibovespa (Sanvicente, 2002). This author argues that such investor behavior would be coherent with agency theory because it rewards managers with good historical performance and punishes those with inferior performance, but, on the other hand, it is irrational, as past performance should not be an indicator of future performance.…”
Section: Determinants Of Brazilian Stock Fund Performancementioning
confidence: 98%
“…This article makes new contributions by using unobservable information, represented by the return gap, to study the choice of stock funds in the Brazilian market, although similar analyses have been made for the U.S. market. It also therefore contributes by extending the literature on investors' decision-making process regarding managers and stock funds, with the employment of the metric that represents information that previous Brazilian studies have not been able to consider as they have been limited to funds' public and objective characteristics and their historical data (Mendonça et al, 2017;Oliveira & Souza, 2015;Sanvicente, 2002;Silva et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the study by Sanvicente (2002) is particularly noteworthy, exploring whether the performance of the São Paulo Stock Exchange Index (IBOVESPA) was crucial for net mutual fund flows in Brazil. Conducted from June 30, 1999 through to June 29, 2001 and based on daily data, this study found that the behavior of the Index up to three days earlier influenced net flow by mutual funds.…”
Section: Review Of the Literaturementioning
confidence: 99%